2021
DOI: 10.3390/diagnostics11091529
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Isokinetic Strength Deficit in Patients with Neurogenic Thoracic Outlet Syndrome

Abstract: Neurogenic thoracic outlet syndrome (NTOS) is an impairing painful condition. Patients usually report upper-limb pain, weakness and paresthesia. Shoulder weakness is frequently reported but has never been described with objective strength evaluation. We aimed to compare isokinetic shoulder strength between patients with NTOS and healthy controls. Patients and controls were prospectively evaluated with an isokinetic strength test at 60 and 180°/s, and an endurance test (30 repetitions at 180°/s) of the shoulder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…As previously published, we confirmed a grip strength deficit on the symptomatic hand of about 12% compared to the asymptomatic side (18). We also found a deficit of strength on the key pinch and on the shoulder rotators on the symptomatic upper-limbs, whereas this was not the case in previous works which had found only significant decreases of strength compared to controls but no significant differences between symptomatic and asymptomatic sides, excepted concerning lateral rotators endurance (18,19). The differences in the current study may be due to the greater number of included subjects from +30 to +53%, which can account for a stronger statistical power.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As previously published, we confirmed a grip strength deficit on the symptomatic hand of about 12% compared to the asymptomatic side (18). We also found a deficit of strength on the key pinch and on the shoulder rotators on the symptomatic upper-limbs, whereas this was not the case in previous works which had found only significant decreases of strength compared to controls but no significant differences between symptomatic and asymptomatic sides, excepted concerning lateral rotators endurance (18,19). The differences in the current study may be due to the greater number of included subjects from +30 to +53%, which can account for a stronger statistical power.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, Daley et al (19) also showed a severe isokinetic strength deficit of the medial and lateral shoulder rotators. Thereby, these two studies highlighted the interest of proximal and distal upper-limb strength measurement in the evaluation of NTOS (18,19). In fact, hydraulic hand dynamometers and pinch gauges can reliably assess strength at the hand level (20-22), and isokinetic shoulder testing can provide accurate and reliable evaluations to measure shoulder strength, especially for medial and lateral rotator muscles (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…V-TOS can be suspected in case of arm swelling with discoloration and heaviness, and abnormal visibility of the chest venous collaterals ( Illig et al, 2016 ). N-TOS diagnosis is more difficult with multiple symptoms, usually including pain, arm weakness, and strength deficit ( Fouasson-Chailloux et al, 2021a ; Daley et al, 2021 ), but the CORE-TOS study group has proposed diagnostic criteria in 2013 and 2016, such as symptoms present for at least 12 weeks, extending beyond the distribution of a single cervical nerve root or peripheral nerve and, that had not been satisfactorily explained by another condition and met at least one criterion in at least four of five specific categories ( Thompson et al, 2013 ; Thompson, 2021 ). In these criteria, only two provocative maneuvers have been retained: the upper limb tension test (ULTT) and the 3-min elevated arm stress test (EAST).…”
Section: Introductionmentioning
confidence: 99%
“…The description of “Gilliatt-Sumner-hand” in 1970, associating a cervical rib with hypothenar or thenar atrophy, is currently considered one of the many features of thoracic outlet syndrome [ 8 , 15 , 27 ]. This finding is scarce in wide cohorts of NTOS patients, even though weakness and decreased endurance have been described [ 5 , 6 ]. Most patients display only subjective symptoms linked to intermittent compression, and have no clinical deficit on examination [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenic TOS (NTOS) represents approximately 90% of patients with thoracic outlet syndrome [ 1 , 3 , 4 ]. It is an impairing and painful condition, responsible for a lack of force and endurance, both at the proximal and distal upper-limb level [ 5 , 6 , 7 ]. NTOS diagnosis remains challenging because it is based on the exclusion of other diagnoses, and on symptoms and clinical examination [ 2 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%